A Critical Appraisal of the Continuity and Elusiveness of the Concept of Development in Post-apartheid South Africa - Ntini, Edmore (African Journal of Development Studies, 2024)
In this paper, I foreground the view that, as human agents initiating and participating in developmental projects that are both economically and educationally oriented, the possession of social consciousness of what development in society in the twenty-first century fully entails is an indispensable attribute. This paper, therefore, interrogates the narrower views of development, which tend to focus on identifying development with the growth of a gross national product with the rise in personal incomes, with industrialisation, or with technological advance (Sen, 1999:3). Thus, I argue that social consciousness on the part of human subjects, who are in turn agents of social developmental change, is critical since development …requires partnerships within a framework of common values and goals (Badat, 2009:11). It is against this backdrop, therefore, that Coppedge’s (1999:465) averment to the effect that “development is more than just average wealth”. Arguably, it is rendered intelligible since “development is a process of expanding the real freedoms that people enjoy”, which ‘contrasts with the narrower views of development’ (Sen, 1999:3). Thus, societies that are bedevilled by social ills resulting from a lack of development must continue to ‘search for human agency and for the means through which inequality can be undone (Hammami, 2006).